(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
The article discusses the use of statistical indices in the analysis of mass social phenomena in various directions. An analysis of the application of the index method in solving an economic problem is carried out. Indices allow you to calculate and measure complex socio-economic phenomena, create mathematical models and conduct economic calculations. By means of the index method, heterogeneous units of the statistical population are combined into a single whole, as well as the decomposition of the phenomenon under study into its constituent elements, and the influence of individual elements and factors on its change is assessed.